Grammatical Interference from English into Indonesian Language Made by English Native Speakers in Salatiga - Asti Supriyanto, Ratih (State Institute of Islamic Studies Salatiga, 2013)
This research was carried out the syntactic interference from English to Indonesian language made by English native speakers in Salatiga. This study was also intended to find out morphological interference from English to Indonesian language made by English native speakers in Salatiga. The research method used was interviewing, recording and transcribing. This method was applied by interviewing English native speakers, then the writer recorded and transcribed to find out the interference that they made. After the data had been collected and analyzed, the writer finds several sub-classifications in syntactic interference as the following: (1) sentence; (2) phrase; (3) diction; and syntactic interference are dominated by phrase, because the phrase construction of English and Indonesian language is different. The construction phrase of Indonesian language is head word + modifier, but in English head word is put after the modifier. Meanwhile for morphological interference is dominated by applying the base form in using the verbs in sentence. The construction of verb in English does not need the inflectional morphology to make the sentence clear as the Indonesian language. The speakers have a tendency to use the base form to show the verb in Indonesian sentence. Keywords: Interference; Syntactic interference; Morphological interference.Â